Educação infantil: aprendizagens de diretoras iniciantes - Mello, Marcia Maria de (Universidade Federal de São Carlos, 2008)
The present study is a qualitative survey involving four preschool directors who are just starting their careers within the community school system. It intends to describe and analyze the acquisition of professional knowledge experienced by these four professionals as they commence their practical living in the school routine. The concept of career is herein understood as a continuous build-up process that spans the entire professional life of an individual. The data used in this survey originated from the analysis of official records, like legal documents and government acts, and from the answers that the directors provided to semi-scripted interviews. The study is based on the hypothesis that preschool directors undergo singular periods of dense and conflicting occurrences as they start their professional practice; in face of such challenges, they often base their decisions upon experiences they had previously, when they were teachers who either observed or were directly helped by experienced directors. The initial period of a director s career is therefore similar to the initial stages of a teacher s career. General aspects of this hypothesis are confirmed as the directors describe details of their path from the teaching context to the management context, especially the strategies they adopted in face of the management challenges. The guiding role played by the more experienced peers is strongly highlighted by all four subjects as being an essential element to that particular moment in their careers. Progress to a further stage in the career is achieved through the particularization of professional skills acquired while performing the managerial work; the perception of being a director is constructed as they find a personal and unique way to pursue their new professional path. Reports collected from the interviews revealed that office and paperwork are likely to take up most of a director s available time during the initial stages in the career, and may be an obstacle to the completion of pedagogic tasks. The way each subject will handle this difficulty is characterized by an individual bias, which will further determine a typical way of running the job. The absence of an institutional development plan was found to be a possible threat to running the pedagogic duties, and the streamlining of both administrative and pedagogic demands may be a valuable aid to career-beginning directors. The skills acquired during professional practice were found to be chiefly related to the managerial context: leadership, team working, conflict resolution, and decision making, among others. This work focuses on the process that eventually leads to the acquisition of such skills and hence to a level of stability in the career of a school director.
Keywords: Escolas - organização e administração; Diretoras iniciantes; Gestão educacional; Educação infantil; Beginning directors; Management; Preschool education; CIENCIAS HUMANAS::EDUCACAO